Effect of Burnout on Performance of Marketing Employees - Anwar, Khoirul; Sutisna, Ade Jaya; Kusnady, Diding; Marthalia, Lia; Dera, Firman (LPPPIPublishing, 2024)
Human resources from time to time have always been interesting for researchers because they provide several benefits for companies, employees, and society. This indicates that the existence of human resources in a company has an important role in achieving goals. This research aims to analyze effect of burnout on performance of marketing employees. This research uses a causal research type with a quantitative approach. The population in the study were employees in the marketing field. Samples were taken randomly to answer the hypothesis of 30 respondents. The method of data analysis in this study used simple linear regression analysis. Based on the research results show that burnout has a positive and significant effect on performance of marketing employees.